Nursing Intervention for Caregivers of Post Autologous Bone Marrow Transplantation Patients at Home (Medico Legal Update, 2021)
Background: Autologous bone marrow transplantation is a curative procedure forhematological diseasesand immune deficiencies. The unique and intensive nature of this treatment requires distinctive care duringand post the entire transplant course. Nursing intervention for caregivers post autologous bone marrowtransplantation patients at home is an important component of the care that improves and develops knowledgeand practice of the caregivers, to take care of the patients in order to help them followthe demanding treatmentplan to reach recovery.Aim to evaluate the effect of nursing intervention for caregivers of post-autologous bone marrowtransplantation patients at home.Material and Method: A Quasi-experimental study was carried out among convenient sample of 143patients and their caregivers who attended the follow up clinic during the first six months post autologousbone marrow transplantation. The study was conducted among patients and their caregivers in three differenthospitals Sheikh Zayed Specialized Hospital, National oncology institute, and Nasser institute at outpatient’sfollow-up clinics.A self-administered questionnaire of patients and their caregivers’ demographic data,and reported checklist of caregivers’ knowledge and practices toward post-autologous bone marrowtransplantation patients at home.Results: There was astatistically significant difference between pre and post nursing intervention, whichindicate improvement in caregivers’ knowledge and practice post implementation of the nursing interventionprogram, and positive correlation between their knowledge and practice.Conclusion and Recommendations: Although caregivers had adequate knowledge, practice on someaspects, gaps were identified. There is a need for educational interventions and discharge plan to upgradeknowledge and practices of the caregivers of post autologous bone marrow transplantation patient at home.